Karakteristik pelet kayu dari limbah pangkasan teh berdasarkan besaran partikel - Sugeng Harianto; Muhammad Iqbal Prawira-Atmaja; Shabri Shabri; Hilman Maulana; Dr. Dadan Rohdiana; Achmad Imron Rosyadi (Jurnal Penelitian Teh dan Kina, 2018)
Biomass waste potential from tea pruning was high, however the utilization of the waste still low. Forming pellet from the waste was one of means for utilizing it to have value-added. Pelletization is a process of compressing the material to increase density value, calorific value, and to uniform the particle size. The method in tea pruning waste pelletization used because the waste is consists of dry twigs and leaves so it was easier in reducing the particle size as pellet raw material. This research purpose was to identify the wood pellet characteristics of various particle size from tea pruning waste, consisted of water content, ash content, and wood pellet density against calorific value produce. The material used in this research was tea pruning waste available all years in the experimental plantation of Reserach Institute for Tea and Cinchona Gambung that has been dried for three days. Pelletization process starts with reducing the tea pruning waste particle using Chopper machine to acquire dust particles. Afterward, those dust was separated into three treatments, which are, passed sieve number 7 mesh, 14 mesh, and 18 mesh. Calorific value produced from the wood pellet was the main factor from all pelletization process, the result show that the dust passed sieve number 18, which is the smallest particle size, has the highest calorific y value produced in the amount of 4.431 cal/g